2021
DOI: 10.1016/j.mayocp.2020.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Alcohol Consumption and Alcohol-Associated Liver Disease

Abstract: Alcohol-associated liver disease is becoming increasingly prevalent throughout the United States. Previously alcohol-associated liver disease was known to affect men more often than women; however, this gap between the sexes is narrowing. Studies show that women develop liver disease with lesser alcohol exposure and suffer worse disease as compared with men. This review article explores the increasing prevalence of alcohol-associated liver disease in women, reasons for changing patterns in alcohol consumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 56 publications
3
43
0
Order By: Relevance
“…First, although historically men were more likely than women to participate in harmful alcohol consumption, this gender gap has narrowed with young men and women consuming alcohol at similar rates. 18 Second, it is well established that harmful effects of alcohol occur at lower levels of exposure in women compared to men. 19 Furthermore, women with alcohol use disorder (AUD) experience more barriers to AUD treatment and are less likely to engage in treatment compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…First, although historically men were more likely than women to participate in harmful alcohol consumption, this gender gap has narrowed with young men and women consuming alcohol at similar rates. 18 Second, it is well established that harmful effects of alcohol occur at lower levels of exposure in women compared to men. 19 Furthermore, women with alcohol use disorder (AUD) experience more barriers to AUD treatment and are less likely to engage in treatment compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…That is, they were free to correlate without influencing each other during the model-fitting phase (Figure 2). This modeling was sex-specific to correct for structural differences in alcohol consumption between the sexes that are well-established in most populations (16,(18)(19)(20).…”
Section: Latent Growth Curve Modelingmentioning
confidence: 99%
“…Alcohol use is widely known to have a genetic component (16)(17) and substantial interindividual differences, such as sex differences (18)(19)(20). Large epidemiological studies have also found differences and inconsistencies between men and women in the association between drinking at baseline and weight gain (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in pre-clinical ALD research, it is important to consider sex differences, since men and women consume and metabolize alcohol differently, have different risk factors contributing to ALD, and ultimately, have different susceptibility to developing the disease[ 100 ]. Even in mice, there are sex differences in susceptibility to ALD when controlling for alcohol intake, diet, and other factors[ 101 ].…”
Section: Gaps In Knowledgementioning
confidence: 99%